2014
DOI: 10.3126/hprospect.v13i2.11833
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Pattern of Personal Protective Equipment among Industrial Workers of Nawalparasi, Nepal

Abstract: Introduction: With industrialization, radical alterations in the life of many rapidly developing countries are visible. Lack of well designed and appropriate safety measures leads to serious adverse health consequences to the workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 3 publications
2
22
1
1
Order By: Relevance
“…The current study showed further that the majority of participants stated that they were regularly using PPE during their work activities. This current study finding concurs with the findings by [47] regarding the Indian construction industry where 68.1% of the participants indicated that used PPE regularly. However, the current study results differ with [32] study in Tanzania where 90% of the participants indicated that wearing PPE affected productivity which possibly influenced them to choose not to wear PPE.…”
Section: Occupational Health and Safety Provision At The Constructionsupporting
confidence: 68%
“…The current study showed further that the majority of participants stated that they were regularly using PPE during their work activities. This current study finding concurs with the findings by [47] regarding the Indian construction industry where 68.1% of the participants indicated that used PPE regularly. However, the current study results differ with [32] study in Tanzania where 90% of the participants indicated that wearing PPE affected productivity which possibly influenced them to choose not to wear PPE.…”
Section: Occupational Health and Safety Provision At The Constructionsupporting
confidence: 68%
“…Occupational injuries which are the global public challenges [20] are common among building construction workers [21]. All workers in the construction industry should be trained on the proper use of PPE [22] to get them protected from potential occupational hazards [23]. Determining factors associated with PPE utilization among workers is vital for implementing the safety work promotion programs [3].…”
Section: Discussionmentioning
confidence: 99%
“…A similar practice was found in a study among industrial workers in Nawalparasi where only 68.1% were found to use PPE. 19 A difference in knowledge and use of PPE was seen with the welders of Nigeria where only 36% were found to use PPE. 20 The use of PPE was associated with age, educational status, working hours, duration of employment and preservice training.…”
Section: International Journal Of Occupational Safety and Health (Ijosh)mentioning
confidence: 99%